Prokineticin receptor 1 ameliorates insulin resistance in skeletal muscle. Issue 2 (13th November 2020) - Mok, Jongsoo; Park, Tae Sub; Kim, Sunhong; Kim, Daehoon; Choi, Cheol Soo; Park, Joonghoon
Abstract: Type 2 diabetes mellitus may result from insulin resistance in skeletal muscle. Prokineticin receptor 1 (Prokr1) improves metabolic phenotype in adipose tissue and the cardiovascular system; however, its effects on skeletal muscle have not been investigated. We investigated the Prokr1 signaling pathways and its metabolic function in murine myoblast, satellite cells, and their differentiated myotubes. We measured the expression levels of Prokr1 in the skeletal muscle of mice as well as human skeletal muscle cell‐derived myotubes. Prokineticin 2 (PROK2), a ligand of PROKR1, induced calcium mobilization in a dose‐dependent manner and altered the mRNA levels of 578 genes in PROKR1‐overexpressed HEK293T cells. Functional enrichment of differentially expressed genes revealed that PROKR1 activated Gq‐mediated PI3K/AKT and MAPK/ERK signaling pathways in skeletal muscle cells. Prokr1 significantly activated the PI3K/AKT signaling pathway in myotubes derived from C2C12 and satellite cells, regardless of the presence or absence of insulin. Prokr1 also promoted the translocation of glucose transporter 4 (GLUT4) into the plasma membrane. In palmitate‐induced insulin‐resistant myotubes, Prokr1 enhanced insulin‐stimulated AKT phosphorylation, GLUT4 translocation, and glucose uptake. mRNA and protein levels of Prokr1 were significantly decreased in skeletal muscle and white adipose tissue of diet‐induced obese mice, and the amount of PROKR1 protein was significantly decreased in human skeletal muscle cell‐derived myotubes under insulin resistance conditions. Taken together, these results demonstrate that Prokr1 plays an important role in insulin sensitivity and is a potential therapeutic target to ameliorate insulin resistance in skeletal muscle.